Earthquake-induced landslides : initiation and run-out analysis by considering vertical seismic loading, tension failure and the trampoline effect /: initiation and run-out analysis by considering vertical seismic loading, tension failure and the trampoline effect. (2017) - Zhang, Yingbin
No abstract available